2016
DOI: 10.17645/pag.v4i1.456
|View full text |Cite
|
Sign up to set email alerts
|

Debating Europe: Effects of the “Eurovision Debate” on EU Attitudes of Young German Voters and the Moderating Role Played by Political Involvement

Abstract: In the run-up to the elections to the European Parliament in 2014, EU citizens had the unprecedented opportunity to watch televised debates between the candidates running for president of the European Commission. The most important debate was the so-called "Eurovision debate", which was broadcasted in almost all EU member states. In this study we explore the responses of a sample of 110 young German voters, who watched this debate, to the candidates' messages and whether exposure to the debate caused a shift i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 49 publications
0
15
1
Order By: Relevance
“…On the one hand, Spitzenkandidaten are likely to be less well known in the EU context (e.g., Popa et al., 2020). Despite considerable campaign efforts (Schmitt et al., 2015), media attention for pan-European candidates is limited to the domestic context (Schulze, 2016), and pan-European debates have little audience reach (Maier et al., 2016: 57). This implies that voters have less information at hand that would help them formulate opinions about the candidates and ultimately guide their voting decision.…”
Section: The Potential Effectiveness Of Personalized Ep Election Campmentioning
confidence: 99%
“…On the one hand, Spitzenkandidaten are likely to be less well known in the EU context (e.g., Popa et al., 2020). Despite considerable campaign efforts (Schmitt et al., 2015), media attention for pan-European candidates is limited to the domestic context (Schulze, 2016), and pan-European debates have little audience reach (Maier et al., 2016: 57). This implies that voters have less information at hand that would help them formulate opinions about the candidates and ultimately guide their voting decision.…”
Section: The Potential Effectiveness Of Personalized Ep Election Campmentioning
confidence: 99%
“…For instance Maier, Rittberger, and Faas showed that the 2014 eP election debate increased support for deeper eU integration. 26 Since the longest tradition of televised debates is to be found in the USa, most of the research investigating the impact of television debates is based on evidence from american politics. However, scholars are also becoming increasingly interested in the impact in europe, especially in germany and the United Kingdom.…”
Section: Impact Of Television Advertisements and Debatesmentioning
confidence: 99%
“…Most of the candidates for Commission President were perceived more positively by German voters after watching the debate (Dinter and Weissenbach 2015). In addition, exposure to the debate significantly increased favourable opinions about EU integration and reduced fears about the EU (Maier et al 2016). Finally, debates can also have an impact on more general attitudes about the political system.…”
Section: Electoral Competition and Eu Support: Insights From Researchmentioning
confidence: 99%
“…In seven countries, recipients additionally had the opportunity to spontaneously evaluate the candidates during the debate. To do so, they used a web-based RTR push button system (for a description of the system see Maier et al 2016). Using this system, individual positive and negative reactions to candidate messages were recorded on a second-by-second basis.…”
Section: Notesmentioning
confidence: 99%